Morphological Features of Fruits of Various Species of Chilli Peppers - Mňahončáková, Erika; Valný, Patrik; Horčinová Sedláčková, Vladimíra (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
The research focused on Capsicum spp. collection (C. annuum L., C. baccatum L., C. chinense Jacq.) cultivated under green-house conditions and examined in the term of morphological characteristics of quantitative (6) and qualitative (4) traits. Aim of the study was to determine the variability in the morphological fruit characters of 28 cultivars. The results revealed considerable morphological variability between the average weight of fruits (0.32–25.94 g), weight of peduncle (0.01–0.41 g), weight of exocarp (0.24–24.60 g), weight of seed (0.04–2.14 g), weight of ovary (0.17–4.92 g) and number seeds per fruit (14.2–185.8 pieces). A cluster analysis was carried out, and a dendrogram was established. With quantitative variables, 6 groups were obtained. Correlations between morphological variables were also estimated. There were highly significant differences for most quantitative characters. The study showed that the weight of fruits parameters is correlated with the variables related to the weight of exocarp and weight of ovary. High diversity based on qualitative traits was detected for the shape of fruits, the colour of fruits ect. Obtained results confirmed that chilli peppers are suitable germplasm for their cultivation and distribution as ornamental plants, their potential uses and benefits to mankind cover many areas processing into food and nutrition, cosmetics, plant-based insecticides, pharmaceutical or medicine products.